PRINCIPLES OF NON-FORMAL ADULT EDUCATION FROM PERSPECTIVE OF PERMANENT EDUCATION - USM ADMIN (Moldova State University, 2021)
This article addresses the issue of the evolution of principles regarding adult learning and education as an important segment of permanent education/lifelong learning. Emphasis is placed on the peculiarities of non-formal adult education: continuing professional training, general culture training (personal development), training community and civic partici- pation skills. In relation to these particularities, the principles of adult learning and education are analysed and developed, but also some suggestions for valorising on these principles are proposed in the design of adult learning and education process. Keywords: adult education, non-formal education, permanent education, lifelong learning, continuing professional training, personal development.